Corrosion of surface modified AISI 4340 steel in jatropha biodiesel - Maleque, Md. Abdul; Belal, Ahmed Ghazal; Ali, Mohammad Yeakub; Al-razzouk, Maan Hayyan; Ahmed, Abu Saleh (Trans Tech Publications, Switzerland, 2015)
The aim of this paper is to study the effect of jatropha curcas biodiesel on the corrosion behavior of surface modified low alloy steel after modification by TIG torch surface melting technique. The coating layer was produced by preplacement of 1 mg/mm2 TiC particulate into the surface of AISI 4340 steel and at heat input of 1344 J/mm using an electric arc generated from the tungsten electrode that melt the powder with substrate material to form a composite layer. The micrograph of the composite coated surface modified steel showed formation of TiC dendrites that densely populated at the of the melt pool which contributes to the high hardness value. The corrosion behavior of the composite coated steel was studied using tafel extrapolation method in biodiesel environment. The surface micrograph after corrosion test shows pitting corrosion holes as a dominant corrosion phenomenon for AISI 4340 steel. The tafel curve showed reduction of corrosion current density of the surface modified steel compared to the alloy street substrate.